Implementasi Manajemen Nyeri Menggunakan Stretching Exercise pada Asuhan Keperawatan Keluarga Lansia dan Pensiunan dengan Masalah Nyeri Sendi - Mentari, Delia; Fradianto, Ikbal; Tafwidhah, Yuyun (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Joint disease is a disorder characterized by pain in the joints, accompanied by stiffness, redness, and swelling. This condition is not caused by trauma or accidents but by inflammation in the joints. Approximately 335 million people worldwide are affected by joint disease. Some common types of joint diseases include osteoarthritis, pain due to high levels of uric acid (hyperuricemia) in both acute and chronic forms, as well as rheumatoid arthritis. Joint pain is often associated with aging or known as a degenerative disease, thus the prevalence of joint pain in the elderly continues to increase each year. One therapy that can be used to alleviate joint pain is muscle stretching exercise or stretching exercise. This method helps maintain muscle flexibility and strength, thereby reducing tension in the joints and relieving pain. Implements pain management using stretching exercises in family nursing care of elderly and retired families with joint pain problem. The case study was conducted in a family at the developmental stage of the elderly and retirees with joint pain problems which were carried out in the working area of the Kampung Bangka Pontianak Community Health Center with a frequency of 6 meetings. The instruments that are used were SOP stretching exercise checklist sheets and pain scale measurement using the Numerical Rating Scale (NRS). After the implementation of the stretching exercise demonstration for 4 meetings, there was a decrease in the pain scale experienced by respondents from the previous 7 scale (severe pain) to 3 scale (mild pain). Respondents and families were able to remember and demonstrate the stretching exercises that had been taught. The implementation of stretching exercise demonstrations to families of the elderly and retirees with joint pain problems can reduce the pain scale that the elderly felt, so it is hoped that the elderly are able to do stretching exercises independently or with family support. Keywords: Stretching, Joint Pain, Family, Elderly  ABSTRAK Penyakit sendi merupakan gangguan yang ditandai dengan nyeri pada persendian, disertai kekakuan, kemerahan dan pembengkakan. Kondisi ini bukan disebabkan oleh benturan atau kecelakaan, melainkan oleh peradangan pada sendi. Penyakit sendi ini dialami oleh sekitar 335 juta penduduk di seluruh dunia. Beberapa jenis penyakit sendi yang umum adalah osteoarthritis, nyeri akibat tingginya kadar asam urat (hiperurisemia) baik dalam bentuk akut maupun kronis, serta rematoid arthritis. Nyeri sendi seringkali dikaitkan dengan pertambahan usia atau dikenal sebagai penyakit degeneratif, sehingga prevalensi nyeri sendi pada lansia terus meningkat setiap tahunnya. Salah satu terapi yang dapat digunakan untuk mengatasi nyeri sendi adalah latihan peregangan otot atau stretching exercise. Metode ini membantu menjaga fleksibilitas dan kekuatan otot, sehingga dapat mengurangi ketegangan pada sendi serta mengurangi rasa nyeri. Mengimplementasikan manajemen nyeri menggunakan stretching exercise pada asuhan keperawatan keluarga lansia dan pensiunan dengan masalah nyeri sendi. Studi kasus dilakukan pada satu keluarga tahap perkembangan lansia dan pensiunan dengan masalah nyeri sendi yang dilaksanakan di wilayah kerja Puskesmas Kampung Bangka Pontianak dengan frekuensi pertemuan sebanyak 6 kali. Instrumen yang digunakan yaitu lembar ceklist SOP stretching exercise dan lembar pengukuran skala nyeri menggunakan Numerical Rating Scale (NRS). Setelah implementasi demonstrasi stretching exercise selama 4 kali pertemuan, terjadi penurunan skala nyeri yang dialami responden dari yang sebelumnya skala 7 (nyeri berat) menjadi skala 3 (nyeri ringan). Responden dan keluarga mampu mengingat dan mendemonstrasikan kembali stretching exercise yang sudah diajarkan. Pemberian implementasi demonstrasi stretching exercise pada keluarga lansia dan pensiunan dengan masalah nyeri sendi dapat menurunkan skala nyeri yang dirasakan lansia, sehingga diharapkan lansia mampu melakukan stretching exercise secara mandiri atau dengan dukungan keluarga. Kata Kunci: Stretching, Nyeri Sendi, Keluarga, Lansia